METAFORA DALAM ALBUM ROHANI HOPE OLEH HILLSONG WORSHIP (SUATU ANALISIS SEMANTIK) - Jacobus, Fera; Pakasi, Jenny H.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research is entitled â€œMetaphors in the Spiritual Album Hope by Hillsong Worshipâ€ is written to fulfill the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is Metaphor in the spiritual album. The problem of this research is focusing on what are the types of metaphor and meanings of metaphor contained in Hope album by Hillsong Worship. This study uses the theory of Leech (1984) and Lakoff & Johnson (1980). The results showed that found from 17 songs there were 47 lines containing metaphors, 34 lines of concretive metaphor, 8 lines of humanizing metaphor, 4 lines of synaesthetic metaphor and 1 line of animistic metaphor. While the metaphor meaning found in each song's lyrics has the same meaning that equates ideas using target and source. The target as the main subject or idea is emphasized and the source as an equated idea that makes two different metaphor meanings into one metaphor meaning.Â Keywords: Metaphor, Hope, Hillsong Worship, Semantic Analysis